KEMAMPUAN REPRESENTASI MATEMATIS SISWA GAYA KOGNITIF REFLEKTIF-IMPULSIF DALAM MENYELESAIKAN MASALAH OPEN-ENDED - Utomo, Via Okta Yudha; Trapsilasiwi, Dinawati; Oktavianingtyas, Ervin (Department of Mathematics Education , University of Jember, 2017)
Abstract.This research aims to describe mathematics representation ability of students’ with impulsive and reflective cognitive style in solving open-ended problem. Instruments which were used are MFFT, open-ended question, and interview. MFFT test used to categorize reflective-impulsive cognitive style. From MFFT test result obtained 2 reflective students and 2 impulsive students who then tested with open-ended problem and interview in order to knowing subjects’ mathematics representation ability in solving open-ended problem. Based on analysis and discussion can be concluded that students with reflective style fulfilled all of the mathematis representation indicators which are visual representation, expression or mathematics equation and words or written text. Students with impulsive cognitive style only fulfilled some of the mathematics representation indicators which are expression or mathematics equations and words or written text. Keywords: Mathematical representation,reflective, impulsif, open-Ended